Sawah Sebagai Jaminan Hutang Piutang Emas Tinjauan Fiqh Syafi’iyah (Studi di Desa Lembung Kecamatan Galis Kabupaten Pamekasan) - hafidatul hasanah (Journal of Islamic Business Law, 2018)
The purpose of this research is to know how the practice of pawn with rice field as a guarantee of the debts receivable that happened in the village of Lembung sub-district of Galis Pamekasan and also how is syafi’iyah perspective against practice of pawn with rice field as a guarantee of the debts receivable that happened in the village of Lembung sub-district of Galis Pamekasan. This research is empirical research with the Juridical sociological approach and data collection Techniques, namely by means of interviews and the documentation. The results of this study indicate that the practice of pawn with rice field as a guarantee of the debts receivable that happened in the village of Lembung sub-district of Galis Pamekasan. in terms of the pillars of the practice have been met, however, from the requirement to be met in the tenets of this practice are not allowed or included in a damaged condition